Malunited fracture of the body and condyle of the mandible : A Case Report - Yeluri, Ramakrishna (Medknow Publications Pvt Ltd, 2010)
Mandibular fractures are the most common facial fractures seen in hospitalized children and their incidence increases with age. Treatment options include soft diet, intermaxillary fixation with eyelet wires, arch bars, circummandibular wiring, or stents. Alternative options include open reduction and internal fixation through either an intraoral or extraoral approach. Many factors complicate the management of pediatric mixed-dentition mandibular fractures: tooth eruption, short roots, developing tooth buds and growth issues. One major factor is the inherent instability of the occlusion in the mixed deciduous-permanent tooth phase. This case report documents a child in mixed dentition period with a complication arising due to direct fixation of the fractured mandible.